The Effect of Constructive Learning Design for Social Solidarity in History Lesson - Bukhari Bukhari; T.M. Jamil; Hasbi Amiruddin (AL-ISHLAH: Jurnal Pendidikan, 2022)
A social solidarity feeling formation in a national building takes the history education as a medium. A constructive learning model was applied to shape the social solidarity among the pupils in two public Senior High Schools in Eastern Aceh of Indonesia. Using Local hero figure of Aceh, that is Abdurrauf As Singkil as role model, this study got use Joseph Renzulli's The Enrichment Triad Model of the core activities. It has a strategic function in developing the soul and character of the nation and building a better future life. It deals with the curriculum design to foster students' attitudes to learning and problem for the knowledge gain process.  Data obtained revealed that the planning stage, the implementation stage and the evaluation stage. The stage of history learning based on Manuscript of Abdurrauf As-Singkili as students’ Solidarity Enrichment encompasses 5 main activities and Joseph Renzulli's The Enrichment Triad Model of the core activities.